THE IMPLEMENTATION OF D PHASE MERDEKA CURRICULUM IN THE ENGLISH TEXTBOOK - Putri, Tara Andina; Amin, Syarif; Syarif, Andi Rachmawati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study aims to conduct a content analysis of the English textbook "Bright an English 2" with the objectives of the Merdeka curriculum as stated in the learning outcomes that refer to D Phase through the Listening-Speaking element. This study focuses on the material contained in the book and its compliance with the Merdeka curriculum. The data analysis of this study was carried out by specifying objectives, conducting cross-validation for study findings, finding relevant data, creating a coding procedure, and collecting contextual evidence. The data were evaluated using the High, Low, and Null categories. The analysis was conducted on a chapter-by-chapter basis, where the textbook has eight chapters. The findings of this study show that the Listening-Speaking material in the English textbook "Bright an English 2" is still minimal because of the 8 chapters in this book, there are only 3 chapters that have aligned with the Merdeka curriculum D Phase, for the Listening-Speaking element, this textbook still needs additional material because there are still several chapters that do not have Listening-Speaking elements.